Luta pela terra no Sudeste do PA: caso do acampamento Frei Henri - CAMPELO, Lilian Cristina Holanda (2020)
At the Frei Henri camp, located in Curionópolis, about 120 families live in an area of the farm called Fazendinha, name given to the property whose lands were identified as belonging to the Union. After a long judicial process that began in 2012 the farmer was expropriated and Incra, after five years, was able to reintegrate tenure in 2017, a remarkable fact in one of the regions with a long history of violence in the countryside and that presents groups of farmers with strong political organization and economic power. On this aspect it is intended to understand which processes interfered in the reintegration of possession of the property, in addition to the historical context of the region marked by intense agrarian conflicts, the scenario is the guiding thread in the investigation process for the identification of the territorial power dispute in a region marked by violence in the countryside.